Phase Change Materials for Solar Energy Applications - Akbari, Hoda; Ahmed, Hind; Mc Cormack, Sarah (Central West Publishing, 2019)
Increasing levels of greenhouse gas (GHG) emissions and energy dependency on other countries have brought governments to develop and improve various ways of producing energy. There are many different methods of renewable production of energy. Currently, solar photovoltaics are one of the most popular methods and rapidly increasing with a worldwide growth of 60% over 5 years from 2007 to 2012. This is due to fact that solar panels are simply designed products that require low maintenance and are easy to install. Photovoltaic systems can be installed on nearly all terrain permit-ting easy distribution of the energy produced among a community or country assisting resolving local grid issues. Furthermore, they also allow energy independence on a local or even national scale, which is a major geopolitical issue for many countries. Although, before 2010 the electricity produced by a PV system was much more expensive than that produced by wind and geothermal power and up to 6 times more expensive than electricity produced by coal and gas, presently the PV cost has decreased 4-5 times becoming a real alternative in the close future to the fossil fuels. This high cost of PV energy is due to the high cost of PV panels and their low level of efficiency -they only convert 15% to 20% of solar radiation into electricity energy. The applications for photovoltaic (PV) systems differ and they include field, transport and building applications. Over the decade, the incorporation of photovoltaics as an integrated part of buildings has exponentially increased. They are referred to as building integrated photovoltaic systems (BIPV) and have one of the fastest growing markets globally.
Phase Change Materials
PUBLISHED
Keywords: Renewable energy; Solar photovoltaics; Building integrated photovoltaic systems (BIPV); Photovoltaic (PV) systems; International Integration; Nanoscience & Materials; Manufacturing Processes (Industrial Engineeri; Microengineering, micromachining; Numerical analysis